Dramatization in the development of the second grade primary children’s social skills - Oyola Suyón, Beberly (2015)
Taking into account the problems of low level in the development of children’s social skills, a program based on the dramatization technique was applied. It was focused in the development of social skills; this problem is manifested in daily actions. The objective was to determine the influence degree of the program. The population consisted of 69 students of the second grade primary school; and the sample was constituted by 35 participants belonging to the second grade "B" primary school. Among the results of the research, they point to a favourable development of children social skills, as evidenced in a good school climate, more harmonious school coexistence, more assertive communication and above all, good relationships with their partners.